Regulation of Galactolipid Biosynthesis by Overexpression of the Rice MGD Gene Contributes to Enhanced Aluminum Tolerance in Tobacco - Zhang, Meijuan; Deng, Xiping; Yin, Lina; Qi, Lingyun; Wang, Xinyue; Wang, Shiwen; Li, Hongbing (Frontiers in Plant Science, 2016)
Membrane lipid alterations affect Al tolerance in plants, but little is known about the regulation of membrane lipid metabolism in response to Al stress. Transgenic tobacco (Nicotiana tabacum) overexpressing rice monogalactosyldiacylglycerol (MGDG) synthase (OsMGD) gene and wild-type tobacco plants were exposed to AlCl3, and the impact of Al toxicity on root growth, Al accumulation, plasma membrane integrity, lipid peroxidation and membrane lipid composition were investigated. Compared with the wild type, the transgenic plants exhibited rapid regrowth of roots after removal of Al and less damage to membrane integrity and lipid peroxidation under Al stress, meanwhile, the Al accumulation showed no difference between wild-type and transgenic plants. Lipid analysis showed that Al treatment dramatically decreased the content of MGDG and the ratio of MGDG to digalactosyldiacylglycerol (DGDG) in wild-type plants, while it was unchanged in transgenic plants. The stable of MGDG level and the ratio of MGDG/DGDG contribute to maintain the membrane stability and permeability. Moreover, Al caused a significant increase in phospholipids in wild-type plants, resulting in a high proportion of phospholipids and low proportion of galactolipids, but these proportions were unaffected in transgenic plants. The high proportion of phospholipids could contribute to a higher rate of Al3+ binding in the membrane and thereby leads to more membrane perturbation and damage. These results show that the regulation of galactolipid biosynthesis could play an important role in maintaining membrane structure and function under Al stress.